2009
DOI: 10.1080/00048670903179160
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Web-Based Treatment of Social Phobia Without Clinician Guidance

Abstract: The aim of the present study (Shyness 4) was to determine which level of reminder best facilitated a clinician-free Internet treatment for social phobia. Method: A pragmatic randomized controlled trial of an enhanced Internet treatment, with and without weekly telephone reminders, was done. Participants consisted of 163 volunteers with social phobia, who completed six lessons of computerized cognitive behaviour therapy for social phobia with complex automated reminders. Main outcome measures were the Social In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 26 publications
4
97
1
Order By: Relevance
“…Andersson et al [2012a] investigated whether experienced CBT therapists yielded better results 17 studies reported large effects of d > 0.80. Only 2 unguided conditions yielded small to moderate effects [Titov et al, 2008c[Titov et al, , 2009a. In the trials comparing ICBT to a waitlist condition, the controlled effect sizes at post assessment varied between d = 0.74 and 1.38.…”
Section: Internet-based Self-help Versus Face-to-face Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Andersson et al [2012a] investigated whether experienced CBT therapists yielded better results 17 studies reported large effects of d > 0.80. Only 2 unguided conditions yielded small to moderate effects [Titov et al, 2008c[Titov et al, , 2009a. In the trials comparing ICBT to a waitlist condition, the controlled effect sizes at post assessment varied between d = 0.74 and 1.38.…”
Section: Internet-based Self-help Versus Face-to-face Therapymentioning
confidence: 99%
“…7 trials focused on the comparison of internet-based self-help with a waitlist control group [Andersson et al, 2006;Berger et al, 2009Berger et al, , 2010Carlbring et al, 2007;Gallego et al, 2011;Tillfors et al, 2011;Titov et al 2008a,b] whereas 1 study compared ICBT to an online discussion group condition [Andersson et al, 2012a]. 8 studies compared different forms of ICBT, 7 of them focusing on different degrees of clinician guidance [Berger et al, 2011;Boettcher et al, 2012a;Furmark et al, 2009;Tillfors et al, 2008;Titov et al, 2008cTitov et al, , 2009a. 1 study examined ICBT with and without Motivational Enhancement Therapy [Titov et al, 2010a] Boettcher/Carlbring/Renneberg/Berger extent to which they assimilated to the clinical routine setting.…”
Section: Efficacymentioning
confidence: 99%
“…Most studies imply that digitizing CBT in one way or another has great potential. [61][62][63][64] Also, as mentioned earlier, many games and ''playful interventions'' have been developed for therapeutic purposes. [33][34][35][36][37][38][39][40][41][42][43][44][45] However, the use of games as a tool for cCBT is quite uncommon.…”
Section: Resultsmentioning
confidence: 99%
“…Clinician guidance seems to play an important role in treatment outcome: meta-analyses suggest a superiority of guided versus unguided self-help treatments in terms of adherence to treatment and efficacy (Palmqvist, Carlbring, & Andersson, 2007;Spek et al, 2007). Although it should be noted that clinician support does not seem necessary in some cases and positive results have also been reported for unguided self-help programs for SAD (Berger et al, 2011;Titov, Andrews, Choi, Schwencke, & Johnston, 2009). Overall, it can be said that ICBT for SAD produces significant improvements.…”
mentioning
confidence: 99%